Hubungan Dukungan Suami Terhadap Keberhasilan Menyusui Secara Eksklusif Di Puskesmas Nguter Kabupaten Sukoharjo - Sulistyaningrum, Anisa; , Dr. Faizah Betty Rahayuningsih, S.Kep., M.Kes (2016)
Breast Milk (ASI) is a liquid given to the baby directly from the mother's milk after the baby is born. Breast milk is the only food that is best for babies, because the content or nutritional composition is in breast milk is full for the development and growth of the baby. During the first six months of the birth of the baby the best nutrition that is required is exclusive breastfeeding. Many factors can affect the breastfeeding exclusively. This study aims to determine the relationship of husband support towards the success of exclusive breastfeeding. This research was conducted in Puskesmas Nguter Sukoharjo regency. The sample in this research that mothers with babies aged six months and stayed one home with her husband as many as 32 people. The sampling technique using total sampling technique. This research is a quantitative research with cross sectional approach. Data collection techniques using research instruments such as questionnaires. The data processing technique used is chi square by using SPSS.The results of this study showed that mothers who get a good husband support as much as 6.3%. Mothers who get a husband's support category was as much as 40.6%. While mothers who get bad kategoti 53.1%. Mothers who successfully breastfeed Exclusive much as 25%, while women who did not succeed as much as 75%. Statistical analysis showed that there was no relationship between the husband support exclusive breastfeeding in the PHC Nguter Sukoharjo regency with p = 0173 (sig> 0.05). Keywords: Support Husband, exclusive breastfeeding